The Role of Electronic and Phononic Excitation in the Optical Response of Monolayer WS2 after Ultrafast Excitation - Ruppert, Claudia; Chernikov, Alexey; Hill, Heather M.; Rigosi, Albert F.; Heinz, Tony F. (Nano Letters)
Transient changes of the optical response of WS2 monolayers are studied by femtosecond broadband pump–probe spectroscopy. Time-dependent absorption spectra are analyzed by tracking the line width broadening, bleaching, and energy shift of the main exciton resonance as a function of time delay after the excitation. Two main sources for the pump-induced changes of the optical response are identified. Specifically, we find an interplay between modifications induced by many-body interactions from photoexcited carriers and by the subsequent transfer of the excitation to the phonon system followed by cooling of the material through the heat transfer to the substrate.
Keywords: Atomically thin 2D materials; carrier and phonon dynamics; ultrafast spectroscopy

Tunable femtosecond near-IR source by pumping an OPA directly with a 90 MHz Yb:fiber source - Mundry, J.; Lohrenz, J.; Betz, M. (Applied Optics)
Up to 400 mW of near-IR (1370-1500 nm) femtosecond pulses are generated from an optical parametric amplifier directly driven by a Yb:fiber oscillator delivering 100 fs pulses at 1036 nm. The process is seeded by a stable supercontinuum obtained from a photonic crystal fiber. We use a single pass through a 3 mm, magnesium oxide-doped, periodically poled LiNbO3 downconversion crystal to produce a near-IR pulse train with a remarkable power stability of 1.4 % (RMS) during one hour. Tuning is achieved by the temperature and the poling period of the nonlinear crystal.
Keywords: Infrared and far-infrared lasers; Ultrafast lasers; Nonlinear optics; parametric processes; Parametric oscillators and amplifiers; Femtosecond pulses; Fiber lasers; Fused silica; Laser systems; Photonic crystal fibers; Pulse propagation